2005
DOI: 10.1111/j.1464-5491.2004.01410.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrical spinal cord stimulation in the long‐term treatment of chronic painful diabetic neuropathy

Abstract: ESCS can continue to provide significant pain relief over a prolonged period of time with little associated morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
76
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 21 publications
4
76
0
Order By: Relevance
“…Besides the fact that these two RCTs demonstrate a pain-relieving effect for a period of 6 months after the start of SCS treatment, only small observational studies suggest a long-term sustained effect in PDPN (3)(4)(5). In this article, we present the 24-month followup data of our recently published RCT in Diabetes Care (1).…”
mentioning
confidence: 98%
“…Besides the fact that these two RCTs demonstrate a pain-relieving effect for a period of 6 months after the start of SCS treatment, only small observational studies suggest a long-term sustained effect in PDPN (3)(4)(5). In this article, we present the 24-month followup data of our recently published RCT in Diabetes Care (1).…”
mentioning
confidence: 98%
“…Several observational studies suggested that SCS may have a positive effect on pain in PDPN patients, with 23 out of 31 patients (74%) reporting a pain relieving effect of $50% after 1 year of treatment (9)(10)(11)(12)(13). Three studies reported a sustained treatment effect (2-7 years) of SCS in PDPN patients (9,10,14).…”
mentioning
confidence: 99%
“…Three studies reported a sustained treatment effect (2-7 years) of SCS in PDPN patients (9,10,14). As SCS is a relatively expensive therapy (;12,000 Euros per patient) and not without risks, such as technical complications, there is a need for randomized controlled trials (RCTs) confirming its effectiveness in PDPN.…”
mentioning
confidence: 99%
“…In a small study, ESCS has been shown to be effective and safe in the treatment of severe, resistant, painful neuropathy, confirming its place in the contemporary management of chronic intractable pain when all other conventional treatment strategies have failed [103]; the beneficial effects can last many years [104] and the majority of complications are of a technical nature and tend to occur during the first 6 months of implantation.…”
Section: Stimulation Therapiesmentioning
confidence: 99%